Maternal cell contamination in embryonic chromosome analysis of missed abortions. Issue 7 (3rd April 2022) - Ouchi, Nozomi; Takeshita, Toshiyuki; Kasano, Sayuri; Yokote, Ryoko; Yonezawa, Mirei; Kurashina, Ryuhei; Ichikawa, Tomoko; Kawabata, Ikuno; Kuwabara, Yoshimitsu; Suzuki, Shunji
Abstract: Aim: The fetal sample used for embryonic chromosome analysis is often contaminated with maternal cells, making it difficult to evaluate the fetal chromosomes. We examined on the rate of maternal cell contamination and its relationship with maternal information in the embryonic chromosome analysis of missed abortions using the Giemsabanding method. Methods: Chromosome analysis was performed in 200 cases of delayed miscarriages in first trimester between July 1, 2000 and May 31, 2019. Chorionic villi were collected and were analyzed using the Giemsa banding method. Among the 20 cells for which chromosomal examination was performed, cells wherein 46, XX chromosomes were found together with normal male karyotype or abnormal chromosomes were defined as maternal cell contamination. Results: Of the 200 cases analyzed, 136 had abnormal chromosomes. The normal female karyotype ( n  = 52) was four times more prevalent than the normal male karyotype ( n  = 12). Maternal cell contamination was seen in 15.4% of the abnormal chromosome cases and 8.3% of the normal male karyotype cases. There was no significant difference in the gestational age between the contaminated and noncontaminated groups at the time of miscarriage diagnosis. However, miscarriage before fetal heartbeat confirmation was significantly associated with higher maternal cell contamination. Conclusion: We found maternal cell contamination in 15% of all the cases. Moreover, in many cases of the normal female karyotype, it was suspected that only maternal chromosomes were cultured. When performing embryonic chromosome analysis in recurrent miscarriages, we should pay attention to maternal cell contamination and interpret the results accordingly.